(untitled) (Tanzania Journal for Population studies and Development, 2022)
This article is from a study that investigated the interplay among art, ritual objects, and belief systems through which the Wangoni people worshipped their God prior to missionary and colonial interventions. The study focused on the significance and implication of art on paraphernalia such as household tools and personal belongings as ritual objects that were commonly evoked during worship or ritual activities of the Wangoni. The ritual theory informed the study’s framework including its methodology, data collection, analysis and presentation, and the discussion of the findings. Using document analysis, interviews and observation to collect data, the study found that artistically-made objects or tools had a special place in the traditional religious practices and lore of the Wangoni. The Wangoni employed personal belongings and objects of deceased family members to establish contacts in the ancestral realm, as their intermediaries before God. It was also established that in the process of making religious-inspired tools or objects, most Wangoni patrons insisted on the artistic excellence of such objects and tools. It was believed that, firstly, art would increase the uniqueness of the object and signify the status and power it symbolized; and secondly, art would help to inculcate a sense of sanctity of the object or tool depending on its aesthetic outlook associated with the Wangoni’s beliefs in the existence of God in their worship or ritual practices.